(untitled) (Research, Society and Development, 2021)
Introduction: Integrative and complementary therapies are being increasingly sought after in the field of health by the general population almost all over the world and, in Brazil, it is no different. Therefore, this research aimed to identify the integrative and complementary therapies used by health teams in Primary Care, after the publication of the National Policy on Integrative and Complementary Practices, and to verify the role of Nursing in the use of therapies. Materials and Methods: Exploratory-descriptive research, with a qualitative character. This is a bibliographical review with scientific articles published from 2008 to 2018, by consulting the Lilacs, Scielo and Capes databases. It was found 11 articles related to the topic. Results and Discussion: It was possible to perceive the constant search for comprehensive care by health professionals to identify and meet the real needs of users who seek the service, using integrative and complementary therapies. Conclusion: This research identified the need to strengthen the work process in health teams so that it has attended to seek a re-evaluation to keep the actions taken under discussion so that its essence is not lost, including the necessary steps to take advantage of therapies in its entirety.